Penerapan Metode Waterfall pada Perancangan Sistem Informasi Pendaftaran Siswa Baru - Badrul, Mohammad; Ardy, Rizkyan (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Education is an effort to develop and develop the potentials possessed by humans because human existence cannot be separated from the environment. One of the institutions to develop human potential is school. school is a center of learning and as a process of socializing and cultivating abilities, values, attitudes, character, and behavior can only occur with conditions of infrastructure, education personnel, curriculum system, and the community environment. SMK Cengkareng 1 is a private educational institution located in West Jakarta. The process of admitting new students at SMK Cengkareng 1 is still done conventionally, where prospective students come to school to register. The new student admission system that occurs at SMK Cengkareng 1 is still inefficient. Because the forms that have been filled in by prospective students must be rewritten into Microsoft Excel, as well as documents that make it difficult for the committee to search for data. One of the efforts to improve the New Student Admissions process and improve services to prospective students, we need a system that can carry out the New Student Admissions process that is not limited by place. One technology that can solve this problem is by utilizing website technology. The Waterfall method is a software development method that allows system building to be carried out in a structured and systematic manner (sequentially) according to the existing development cycle. With this system, it is hoped that it can help prospective students and the committee in the process of admitting new students.